Pengaruh urea dalam media maturasi in vitro terhadap tingkat maturasi oosit sapi - Kurniawati, Sepvian Dewi; Sarudji, Suryanie; Widjiati, Widjiati (Universitas Airlangga, 2021)
This study was aimed to determine the effect of urea in maturation medium on in vitro oocyte maturation rate. The medium used was TCM-199 added with Hepes, NaHCO3, Kanamycin 0.15 IU/mL, PMSG, 0.15 IU/mL hCG, and 10% FBS. Cumulus oocyte complexes (COCs) of cows derived from follicle aspiration were divided into three groups. In control group (P0), the COCs were matured in vitro in a maturation medium without urea addition, meanwhile in the P1 and P2 groups, the medium was added with urea 20 and 40 mg/dL, respectively. Each petri dish contained three drops of maturation medium (300 µl/drops) according to the groups. Microdrops were coated with mineral oil and then incubated in a 5% CO2 incubator, at 39 ËšC with maximum humidity. Aceto-orcein staining was conducted to evaluate the maturation of oocytes based on the achievement of metaphase II phase that is indicated by the presence of metaphase plate and/or first polar body. The result showed that the oocyte maturation rates of P0, P1, and P2 were 51.25, 52.43 (p >0.05), and 46.88 % (p <0.05) respectively. It could be concluded that the presence of urea at 40 mg/dL in maturation medium reduced the percentage of bovine oocyte maturation in vitro.